2021
DOI: 10.1038/s41598-021-92423-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thinning and understory removal on the soil water-holding capacity in Pinus massoniana plantations

Abstract: Forest management practices play an important role in regulating the soil water-holding capacity of plantation. However, most studies focus on soil water dynamics present during large-scale forest loss and afforestation events, while little is known about how soil water under different forest management practices responds to rainfall events and which factors mainly regulate soil water-holding capacity. In this study, a stable hydrogen isotope was used to explore the contribution of three natural rainfall event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
3
10
1
Order By: Relevance
“…However, superabundant mother culms in high-density stands caused increased competition for nutrients, water, sunlight, and stand space [31][32][33] and were not conducive to increased bamboo-shoot yield. Secondly, density management can change soil physical and chemical properties, affecting crop yield [15,34,35]. In our study, soil-nutrient content increased and then decreased with increasing stand density (Tables A1 and A2), which was almost consistent with the changes in shoot yield and density.…”
Section: The Bamboo-shoot Yieldsupporting
confidence: 80%
“…However, superabundant mother culms in high-density stands caused increased competition for nutrients, water, sunlight, and stand space [31][32][33] and were not conducive to increased bamboo-shoot yield. Secondly, density management can change soil physical and chemical properties, affecting crop yield [15,34,35]. In our study, soil-nutrient content increased and then decreased with increasing stand density (Tables A1 and A2), which was almost consistent with the changes in shoot yield and density.…”
Section: The Bamboo-shoot Yieldsupporting
confidence: 80%
“…Contrary to our first hypothesis, short-term (5 years) CNA significantly influenced the composition of soil bacterial and fungal communities ( Supplementary Figures 2 , 3 ). This finding supported most studies of understory N addition ( Freedman et al, 2015 ; Wang T. et al, 2021 ) but was inconsistent with Shi et al (2016) , who found that CNA did not change the composition of soil microbial communities in a subtropical or temperate forest. The difference in experimental duration might explain this inconsistency.…”
Section: Discussionsupporting
confidence: 65%
“…Understory vegetation removal is an important silviculture practice in plantation ecosystems ( Wang T. et al, 2021 ). The understory is removed to reduce competition between tree and understory species and increase lumber production ( Wu et al, 2011 ; Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH value according to a soil-water ratio of 1:5 was measured with a Shanghai Lei Magnetic Multi-parameter Water Quality Analyzer DZS-708. EC was measured in the soil at a depth of 10 cm using a FieldScout EC450 m. Maximum moisture capacity, capillary capacity, and field capacity (FC) were measured using the cutting ring method without compaction treatment (Wang et al, 2021). Total phosphate (P) content was measured using ICP-MS after microwave digestion (MARS5, CEM, United States) (0.1 g sample + 6 mL concentrated nitric acid).…”
Section: Sample Analysismentioning
confidence: 99%